SUPERVISI KEPALA SEKOLAH MEMODERASI PENGARUH KOMITMEN DAN KOMPETENSI TERHADAP KINERJA GURU MTsN KABUPATEN PATI - S u y o n o, 12 5202 0006; Sutomo, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine the moderating influence of the principal supervision of organizational commitment and personal competence of the teachers performance in MTs.N Pati . The research was conducted on the teacher at MTs in Pati as many as 109 respondents , using the data collected by the census technique . A statistical technique is used to test the validity of the component matrix , Cronbach alpha reliability test , test with the adjusted r Â² r square and t tests . Â Test results obtained hypothesized that 1 ) no significant effect of organizational commitment on teacher performance , 2 ) the competence of the teacher s personality and a significant positive effect on teacher performance , 3 ) supervision of the principal positive and significant effect on the performance of teachers , 4 ) Supervision of the principal does not moderate the effect of commitment to teacher performance , and 5 ) the principal supervision does not moderate the effect of teacher competence on teacher performance in MTs N Pati . Keywords : Â Organizational Commitment , Competence Kepribadin , Supervising Principal , and Performance